Osteoarthritis Literacy and Equity Issues: A Post COVID-19 Analysis and Update - Marks, Ray (Journal of Aging Research And Healthcare, 2022)
Background Osteoarthritis, the most common joint disease and one affecting a large number of older adults is not always amenable to the use of passive interventions such as surgery or pharmacologic interventions, but even then, to maximize any desirable intervention approaches, a trustworthy and supportive partnership with the sufferer is strongly indicated. Complicating this process are emerging equity and persistent health literacy issues, as well as post COVID-19 service associated ramifications and persistent disease risks. Aim This mini review was designed to examine what current data reveal as regards the presentation of osteoarthritis and its pathology among the older adult as of the current post COVID-19 pandemic period in 2022, and how health literacy and equity issues are likely implicated in some degree with the disease presentation and its outcomes and will be likely to continue, unless remediated. Methods Peer reviewed published articles on this topic were sought from multiple data bases using the key words- osteoarthritis, health equity, health literacy, prevention, and intervention. Results As in prior years, osteoarthritis continues to induce considerable physical disability and consistently impedes the attainment of a high life quality for many older adults. Although not studied to any degree, attention to health equity and literacy issues appear to pose additional osteoarthritis intervention challenges, especially among the long COVID affected older adults and those with low income and educational levels. Conclusions Many behaviourally oriented and necessary osteoarthritis management approaches and interventions may fail to reduce the functional disability and pain experienced by older people with any form of osteoarthritis to any meaningful degree if a) the provider does not tailor their recommendations in light of possible prevailing health literacy, economic, and educational challenges; b) the patient does not understand how their health behaviours impact joint disease as well as COVID-19 risk status, and are not empowered to undertake these.
Keywords: Aging; Disability; Equity; Health Literacy; Intervention; Osteoarthritis; Outcomes; Prevention